Southern Photographs 02 : Zed Nelson - Cera, Michele (s.l. : LAB - Laboratorio di Fotografia di Architettura e Paesaggio, 2013)
Lachi, Marco ; Colella, Francesco ; Brescia, Daniele ; Grittani, Aldo ; Lacarbonara, Orlando ; Lastrucci, Massimo ; Vinsentini, Giuseppe ; Catania, Corrado ; Tartaglione, Antonio ; Rossiello, Fabrizio et al.
This publication covers a part of the photographic work produced during the 'Southern Photographs 2' workshop held in june 2013 in Cisternino. Twentytwo photographers, coming from different areas of Italy, explored the territory between Cisternino and the seaside. 'Southern Photographs 2' is the second of a series of international photography workshops that the Cultural Association LAB is carrying out of Puglia. (from the cover of the last page)
Publication consists of loose pages
boek
Keywords: Nelson, Zed